2012
DOI: 10.2174/187569212802509997
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Heterogeneity in Supplementation Effects of Selenium in Men: A Study of Stratification Variables and Human Genetics in a Prospective Sample from New Zealand

Abstract: There is marked controversy on the beneficial levels of selenium (Se) to be used as a dietary supplement. The form of supplemented Se and the baseline plasma or serum Se status among supplemented populations are generally considered as crucial factors in this controversy. However, responses to supplemented Se can further vary with other factors, including health status, lifestyle, demographics and genetics. In the present study, the putative supplementation benefits of Se as 200 µg/day selenised yeast for six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 80 publications
(99 reference statements)
4
10
0
Order By: Relevance
“…Our studies have also shown that optimal levels of serum selenium towards minimizing DNA damage are recorded between 116 and 150 ng/mL which also have genetic influences [15]. The influence of age and BMI in influencing serum selenium retention was reported by us previously [16]. We have also shown that a 200 µg/d selenium supplementation benefits by way of DNA damage reduction is achieved dependent on dietary methionine and folate levels and BMI [16,17].…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our studies have also shown that optimal levels of serum selenium towards minimizing DNA damage are recorded between 116 and 150 ng/mL which also have genetic influences [15]. The influence of age and BMI in influencing serum selenium retention was reported by us previously [16]. We have also shown that a 200 µg/d selenium supplementation benefits by way of DNA damage reduction is achieved dependent on dietary methionine and folate levels and BMI [16,17].…”
Section: Introductionsupporting
confidence: 75%
“…The influence of age and BMI in influencing serum selenium retention was reported by us previously [16]. We have also shown that a 200 µg/d selenium supplementation benefits by way of DNA damage reduction is achieved dependent on dietary methionine and folate levels and BMI [16,17]. Studies including ours have reported selenium supplementation to lower serum prostate-specific antigen (PSA) levels among men with high-risk for prostate cancer and among middle-aged US men [18,19].…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Whether or not supplementation with SeMet or Se-yeast differentially alters the amount of particular selenium species within the prostate, such as methylselenol or selenoproteins [30,31], could not be determined in our study, because only total selenium concentration was measured. Whether or not host factors, such as age or obesity [32], impact the systemic and intraprostatic concentrations of selenium achievable after supplementation with different selenium forms could not be rigorously interrogated in our dogs due to small sample size, but deserves further evaluation.…”
Section: Discussionmentioning
confidence: 99%